Cation‐π Interactions between a Noble Metal and a Polyfunctional Aromatic Ligand: Ag+(benzylamine). Issue 33 (5th May 2022) - Corinti, Davide; Maccelli, Alessandro; Chiavarino, Barbara; Schütz, Markus; Bouchet, Aude; Dopfer, Otto; Crestoni, Maria Elisa; Fornarini, Simonetta
Abstract: The structure of an isolated Ag + (benzylamine) complex is investigated by infrared multiple photon dissociation (IRMPD) spectroscopy complemented with quantum chemical calculations of candidate geometries and their vibrational spectra, aiming to ascertain the role of competing cation‐N and cation‐π interactions potentially offered by the polyfunctional ligand. The IRMPD spectrum has been recorded in the 800–1800 cm −1 fingerprint range using the IR free electron laser beamline coupled with an FT‐ICR mass spectrometer at the Centre Laser Infrarouge d'Orsay (CLIO). The resulting IRMPD pattern points toward a chelate coordination (N‐Ag + ‐π) involving both the amino nitrogen atom and the aromatic π‐system of the phenyl ring. The gas‐phase reactivity of Ag + (benzylamine) with a neutral molecular ligand (L) possessing either an amino/aza functionality or an aryl group confirms N‐ and π‐binding affinity and suggests an augmented silver coordination in the product adduct ion Ag + ( benzylamine ) ( L ) . Abstract : IR multiple photon dissociation spectroscopy unveils the structure of the Ag + (benzylamine) complex (Ag + (BA)), presenting a N‐Ag + ‐π chelate coordination involving both the amino nitrogen and the phenyl π‐system. The gas‐phase reactivity of Ag + (BA) with neutral molecular ligands (L) confirms N‐ and π‐binding affinity and indicates an augmented silver coordination in the Ag + (BA)(L) adduct.